Effects of triptolide and methotrexate nanosuspensions on left ventricular remodeling in autoimmune myocarditis rats - Li W (Dove Medical Press, 2019)
Wei Li,1 Kaizheng Gong,1 Yuan Ding,2 Birenda Chaurasiya,2 Yue Ni,1 Yong Wu,1 Pei Zhao,1 Yan Shen,2 Zhengang Zhang,1 Thomas J Webster3 1Department of Cardiology, Affiliated Hospital of Yangzhou University, Yangzhou, Jiangsu 225000, China; 2Department of Pharmaceutics, School of Pharmacy, China Pharmaceutical University, Nanjing, Jiangsu 210009, China; 3Department of Chemical Engineering, Northeastern University, Boston, MA 02115, USA Purpose: This study was carried out to investigate the effects of a triptolide (TP) nanosuspension and methotrexate (MTX) nanosuspension on left ventricular remodeling and cardiac function for autoimmune myocarditis (EAM) in rats. The regulating effects on inflammatory cytokines in the peripheral serum and related mechanisms are also discussed. Methods: First, TP and MTX were prepared as a nanosuspension, and the EAM model was successfully established in rats with cardiac myosin. Then, the effect of TP and MTX suspensions was tested in an EAM model. Results: Results revealed that both TP and MTX suspensions could reduce the degree of myocardial fibrosis and delay the remodeling process of the left ventricle which could further improve cardiac function. Finally, it was found that inflammatory cytokines in the peripheral serum were regulated by the nonspecific immune system and the inhibition of nuclear factor-κB signaling might have partly occurred due to this mechanism. Conclusion: In summary, this study provided a complete foundation for EAM therapy of profound clinical relevance. Keywords: inflammatory cytokines, heart failure, dilated cardiomyopathy, immunoregulation, suspension